Ekstrak Daun Tembakau (Nicotiana tabacum) Sebagai Akarisida Pada Caplak (Boophilus microplus) - Nurul Fajriani M; Abdul Wahid Jamaluddin; Adryani Ris (Parapemikir : Jurnal Ilmiah Farmasi, 2019)
Ticks as blood sucking ectoparasites in cattle can cause a variety of diseases, malnutrition to livestock emaciation. One of the natural acaricides is Tobacco which contains Flavonoids, Tanins and Saponins. The purpose of this study was to determine the activity of Akarisida tobacco leaf extract against Boophilus microplus ticks. In this study 50 ticks were used which were then divided into 5 setting groups with each group twice repeated. The negative control group was given 1% Na CMC, the positive control group was given bestrin forte synthetic medicine, group 3 was given 10% Tobacco Leaf Extract (EDT), group 4 was given 15% EDT, and group 5 was given 20% EDT. After spending 2 hours for 6 hours and determine which group will beat the tick the fastest. Data analysis using Anova One Way statistics. Boophilus microplus starts at a concentration of 10%, and the fastest to determine tick (the first 2 hours period is EDT 20%). Keywords— Boophilus microplus, tobacco leaf, tobacco leaf extract, akarisida